Anatomy of Income Inequality in the United States: 1979-2013 - Aboozar Hadavand (Luxembourg Income Study (LIS), 2017)
This paper provides a novel analysis of the trend in income inequality in the United States between 1979-2013. There are two ways in which this paper contributes to the literature. First, I analyze how much of the existing inequality in the U.S. is due to the demographic changes that happened over this period. Using microdata from Luxembourg Income Study and after decomposing inequality into within- and between-age group components, I find that the within-group share of overall inequality in the U.S. is high and steady compared to other developed countries. I also find that about 17 percent of the rise in inequality in this period is due to the between-group component (life-cycle effects). Second, I provide a regression analysis to explain cross-group variations in inequality during the period. I estimate that most of the rise in inequality has happened among middle-aged men while inequality among women, especially among married women has, in fact, decreased. This more granular analysis of inequality can help us investigate the causes of inequality, which would be impossible if we only look at a single inequality statistic.
Keywords: D31; J11; D63; 330; Inequality Decomposition; Within-Group Inequality; Income Distribution